2023
DOI: 10.1111/cea.14281
|View full text |Cite
|
Sign up to set email alerts
|

Is antenatal or early‐life vitamin D associated with eczema or food allergy in childhood? A systematic review

Abstract: Objective To summarise the associations between antenatal or early‐life blood vitamin D and the development of eczema/food allergy in childhood. Design A systematic review and meta‐analyses were conducted to synthesize the published literature. Two reviewers independently performed the study selection and data extraction on Covidence. We assessed the risk of bias for observational studies by using the Newcastle‐Ottawa Scale and the Cochrane Risk of Bias tool for clinical trials. The certainty of the evidence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 87 publications
1
11
1
Order By: Relevance
“…Most cohort studies found no association between vitamin D intake during pregnancy and eczema in their offspring in Western countries [22,[29][30][31]. Indeed, a meta-analysis and a systematic review that included Japanese cohort studies found no significant relationship, as in our study [11,12]. Differences in the effect of vitamin D intake on the development of each disease might be due to the diverse biological activities of vitamin D [6].…”
Section: Maternal Dietary Vitamin D Intake Associated With Offspring ...contrasting
confidence: 49%
See 2 more Smart Citations
“…Most cohort studies found no association between vitamin D intake during pregnancy and eczema in their offspring in Western countries [22,[29][30][31]. Indeed, a meta-analysis and a systematic review that included Japanese cohort studies found no significant relationship, as in our study [11,12]. Differences in the effect of vitamin D intake on the development of each disease might be due to the diverse biological activities of vitamin D [6].…”
Section: Maternal Dietary Vitamin D Intake Associated With Offspring ...contrasting
confidence: 49%
“…For atopic dermatitis, one RCT found a reduction in the OR at 12 months of age with vitamin D supplementation during pregnancy, but no significant difference at 24 or 48 months [37]. Furthermore, a recent meta-analysis of four RCTs, including the above study, found no significant relationship [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention trials have not supported a benefit for vitamin D interventions during pregnancy or infancy on asthma prevention, but the use of vitamin D for eczema and food allergy prevention is less well‐explored 6 . In this month's issue, Zeng et al explore early life vitamin D status and risk of subsequent eczema or food allergy development 7 . They systematically reviewed all cohort studies evaluating 25‐hydroxy‐vitamin D levels in maternal, cord blood or infant blood, maternal or infant dietary vitamin D intake or randomized controlled trials of vitamin D supplementation during pregnancy or infancy.…”
Section: Figurementioning
confidence: 99%
“…MHS approved the manuscript. Robert J. Boyle 1 Mohamed H. Shamji F I G U R E 2 From Zeng et al 7 In a comprehensive and well-conducted systematic review, authors identified a possible relationship between cord blood vitamin D status and future risk of eczema development.…”
Section: Auth O R Co Ntr I B Uti O N Smentioning
confidence: 99%